Implementation of the World Health Organization Global Burn Registry: Lessons Learned. Issue 1 (18th May 2022) - Hebron, Caitlin; Mehta, Kajal; Stewart, Barclay; Price, Patricia; Potokar, Tom
Burn injuries are a major cause of death and disability globally; however, the true epidemiologic burden is underestimated given the limited and fragmented availability of high-quality burn injury data from many regions. To address this gap, the World Health Organization (WHO) Global Burn Registry (GBR)—a minimum dataset aligned with a centralized registry—was officially launched in 2018 to facilitate hospital-level collection of key prevention, care, and outcome data from burn-injured patients around the world in a standardized manner. However, uptake and use of GBR has been low and inconsistent. Therefore, we aimed to identify and understand the barriers and facilitators to the implementation of the GBR to inform the development of a web-based GBR implementation guide through the Centre for Global Burn Injury Policy and Research and Interburns . We designed and conducted web-based surveys with "GBR users" and "GBR non-users" using purposive sampling. Themes of identified barriers and facilitators focused on awareness of the GBR, stakeholder buy-in, resource constraints, process management, and utility of the registry. The lessons learned could support current and future GBR users to promote and maximize the use of the GBR. To achieve the GBR's full potential in global burn injury prevention and care, engagement with the GBR should be enhanced through education and promotion, development of a community of practice, tools for data utilization and quality improvement, and periodic re-evaluation.